Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility